Causal association between gut microbiota and hyperemesis gravidarum: a two-sample Mendelian randomization study - Xu, Dinglin; Zhang, Liang; Zhang, Jianwei (Frontiers in Microbiology, 2024)
Background Observational studies have reported an association between the gut microbiota (GM) and hyperemesis gravidarum (HG). However, the causal relationship is unclear. In this study, Mendelian randomization (MR) was used to infer causal relationships between GM and HG.Methods Inverse-variance weighted MR was performed using summary statistics for genetic variants from genome-wide association studies (GWAS). Sensitivity analyses were performed to validate the MR results and assess the robustness of the causal inference. Reverse MR analysis was performed for bacterial taxa that were causally linked to the HG risk in the forward MR analysis to evaluate reverse causality. Results MR analysis revealed that the genera Defluviitaleaceae UCG011, Ruminococcus1, Ruminococcus2, Turicibacter, and unknowngenus and phylum Verrucomicrobiota are positively associated with the risk of HG. Additionally, the genus Coprococcus2 was related to a decreased risk of HG. Sensitivity studies validated the strength and reliability of the link between the composition of the GM and HG. No evidence for reverse causality from HG to identified bacterial taxa was found. Conclusion Our MR analysis provided novel insight into the association between GM and HG. In particular, our results indicated that targeting the GM could serve as an effective therapeutic strategy for HG.